Novel e4a2 BCR∷ABL1 transcript with insertion of CSE1L exons 9 and 10 in a CML patient: a case report - Di Giusto, Sara; Toffoletti, Eleonora; Cozzarolo, Cinzia; Liani, Tomas; Moro, Moira; Fanin, Renato; Damiani, Daniela; Tiribelli, Mario (Frontiers in Oncology, 2025)
The BCR::ABL1 fusion gene, resulting from the Philadelphia (Ph) chromosome, is the defining feature of Chronic Myeloid Leukemia (CML). The fusion transcript typically results from the juxtaposition of ABL1 exons 2 or 3 and BCR exons 1, 13, 14 or 19, while exons 6 and 8 are less frequently involved. Here, we report the first case of a translocation in a patient with newly diagnosed chronic-phase CML harboring a novel e4a2 BCR::ABL1 fusion gene. This unique fusion includes a 298 bp insertion, derived from a CSE1L gene exons 9 and 10, at the fusion site. The patient showed resistance to first-line dasatinib but achieved a molecular response with the third-generation tyrosine kinase inhibitor ponatinib.